2004
DOI: 10.5194/angeo-22-4165-2004
|View full text |Cite
|
Sign up to set email alerts
|

Thinning and expansion of the substorm plasma sheet: Cluster PEACE timing analysis

Abstract: Abstract. The storage and subsequent removal of magnetic flux in the magnetotail during a geomagnetic substorm has a dramatic effect on the thickness of the cross-tail plasma sheet. The near-Earth plasma sheet is thought to thin during the growth phase and then rapidly expand after onset of the substorm. The direction of propagation, whether earthward or tailward along the GSM-X direction in the near-Earth tail, may suggest the time ordering of current-disruption and near-Earth reconnection, both of which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…Previous analysis showed that the thinning sheet boundary velocity evaluated from the timing at two spacecraft (ISEE-1,2) was consistent with simultaneously observed inward (upward in our case) plasma flow velocity [Forbes et al, 1981]. A recent timing study by Cluster [Dewhurst et al, 2004] gave the typical thinning speeds of 10 -70 km/s and confirm that fast thinnings are the expansion-related (rather than growth phase-related) phenomena. In a few cases the fast thinnings were observed as close to the Earth as 9 Re (Polar observations at 2107 UT on 8 September 2002 presented by Sergeev et al [2005]) or even $7 Re (initial thinning at TC2 before the subsequent plasma sheet expansion occurred 1 min later [Sergeev et al, 2008]).…”
Section: Expansion Onset Process As Seen By the Observer At The Lobe supporting
confidence: 88%
“…Previous analysis showed that the thinning sheet boundary velocity evaluated from the timing at two spacecraft (ISEE-1,2) was consistent with simultaneously observed inward (upward in our case) plasma flow velocity [Forbes et al, 1981]. A recent timing study by Cluster [Dewhurst et al, 2004] gave the typical thinning speeds of 10 -70 km/s and confirm that fast thinnings are the expansion-related (rather than growth phase-related) phenomena. In a few cases the fast thinnings were observed as close to the Earth as 9 Re (Polar observations at 2107 UT on 8 September 2002 presented by Sergeev et al [2005]) or even $7 Re (initial thinning at TC2 before the subsequent plasma sheet expansion occurred 1 min later [Sergeev et al, 2008]).…”
Section: Expansion Onset Process As Seen By the Observer At The Lobe supporting
confidence: 88%
“…The unit normal at which the Cluster spacecraft cross the PSBL to return to the lobe indicates that it is inclined mainly in the y-z plane, with both y and z-components negative. The boundary is travelling at 38 km/s −1 which is faster than the previous entry but again slower than typical values previously found (Dewhurst et al, 2004).…”
Section: Discussionsupporting
confidence: 47%
“…The unit normal at which the spacecraft cross the PSBL into the plasma sheet at 19:03 UT indicates that it is inclined mainly in the y − z plane, with a negative y-component. The boundary is travelling at 30 km/s −1 which is slower than typical values (Dewhurst et al, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…The ratio of the plasma sheet cross‐tail area ( 2RTΔ) to the total cross‐tail area ( πRT2), equal to 2Δ/ π R T , can reach ∼15% in the midtail. Note that the latter value may considerably change in the course of substorms [ Baumjohann et al , ; Sergeev et al , ; Dewhurst et al , ; Petrukovich et al , ] and during a bursty bulk flow (BBF) passage [ Panov et al ., ].In view of the above caveats, the algorithm gives an upper estimate of the total magnetic flux through the given tail cross section. Neglecting the finite width of plasma sheet, where the magnetic field lines are closed and the magnetic field magnitude is lower than in the lobes, is unavoidable at the moment.…”
Section: Magnetotail Magnetic Flux Calculationmentioning
confidence: 99%
“…The ratio of the plasma sheet cross-tail area (2R * T Δ) to the total cross-tail area ( R 2 T ), equal to 2Δ∕ R T , can reach ∼15% in the midtail. Note that the latter value may considerably change in the course of substorms [Baumjohann et al, 1992;Sergeev et al, 1993;Dewhurst et al, 2004;Petrukovich et al, 2011] and during a bursty bulk flow (BBF) passage [Panov et al, 2010]. In view of the above caveats, the algorithm (1)-(5) gives an upper estimate of the total magnetic flux through the given tail cross section.…”
Section: 1002/2016ja022911mentioning
confidence: 99%